2018
DOI: 10.22226/2410-3535-2018-3-299-304
|View full text |Cite
|
Sign up to set email alerts
|

Localized magnetic inhomogeneities generation on defects as a new channel of damping for a moving domain wall

Abstract: The paper presents theoretical studies on the domain wall energy losses that arise when it moves through the magnetic defect region. These losses are largely related to the generation of localized magnetization waves in the defect region. It is shown that the process of the domain wall energy scattering on the defect can be regarded as a new "channel of damping" for a domain wall. The study was carried out using numerical and analytical methods through the example of a three-layer model of the ferromagnetic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…In this case the DW should change its shape significantly when passing through the thin magnetic layer. In these systems pinning of domain walls, generation of localized magnetization waves, such as magnetic solitons and breathers, generation of spin waves are possible [7,12,14,[23][24]. It is worth to note that two-dimensional magnetic inhomogeneities of magnetic vortex type near the inhomogeneities of the magnetic anisotropy also demonstrate a diversity of their behavior: pinning of the vortex by defect with explicit change in the rotation speed, reflection before defect with different motion paths, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the DW should change its shape significantly when passing through the thin magnetic layer. In these systems pinning of domain walls, generation of localized magnetization waves, such as magnetic solitons and breathers, generation of spin waves are possible [7,12,14,[23][24]. It is worth to note that two-dimensional magnetic inhomogeneities of magnetic vortex type near the inhomogeneities of the magnetic anisotropy also demonstrate a diversity of their behavior: pinning of the vortex by defect with explicit change in the rotation speed, reflection before defect with different motion paths, etc.…”
Section: Introductionmentioning
confidence: 99%
“…В связи со сложностью задачи, даже для одномерного случая, исследователями рассматривалась, как правило, модуляция лишь отдельных параметров магнитной системы. Часто учитывалась, например, модуляция магнитной анизотропии [15,16,20]. При определённых условиях, изучение одномерной динамики магнитных неоднородностей приводит к интересной и с математической точки зрения задаче нахождения решения нелинейного дифференциального уравнения типа синус-Гордона с переменными коэффициентами, имеющего важное значение для многих областей современной физики [21].…”
Section: Introductionunclassified
“…The work [22] has shown that this effect can be observed under certain conditions even in the presence of damping that always occurs in real physical systems. The value of energy consumed for the excitation of localized waves by the kink will determine the value of a new contribution to the effective damping of a moving kink [45]. It may change depending on its initial velocity.…”
Section: Introductionmentioning
confidence: 99%